Effect of Season on Physico-Morphological Attributes of Cryopreserved Hariana Bull Spermatozoa - Singh, Vipin; Kumar, Anuj; Yadav, Chhote Lal; Patel, Akhil; Yadav, Brajesh; Saxena, Atul (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
The present study was undertaken to evaluate the effect of seasonal variations on various seminal attributes and freezability of Hariana bull semen. The study was conducted over a period of four months and divided into two peak seasons as winter (December-January) and summer (May-June). Twenty-four ejaculates were collected from 4 bulls in each season. The physico-morphological characteristics of semen, viz., volume (ml), mass activity (0-5 scale), pH, sperm concentration (million/ ml), progressive motility (%), sperm livability (%), HOST (%), total morphological sperm abnormality (%) and acrosomal integrity (%) were estimated at different stages of cryopreservation in different seasons. During summer season the ejaculate volume and seminal pH were found non-significantly higher than in winter, whereas the percentage of morphologically abnormal spermatozoa was significantly (p<0.05) higher in summer. Post thaw percentage of progressively motile spermatozoa was significantly (p<0.05) higher in winter than summer season. Live sperm per cent were significantly (p<0.05) higher in winter than summer season both at fresh and pre-freeze stage. HOST positive sperm and acrosomal integrity were significantly (p<0.01) higher in winter season than summer at all three stages. The study generated basic information that the summer season adversely affects the various physico-morphological characteristics of Hariana bull semen altering its freezability. important tool for breeding purposes, has always Hariana is one of the most prominent dual purpose cattle breed of Indo Gangetic plain and is well adapted to the tropical environments, mainly because of the high degree of heat tolerance and resistance to many tropical diseases. The indigenous breeds, which traditionally form an integral part of agriculture, are decreasing in number in last couple of decades due to mechanization of agriculture. For conservation of this valuable germplasm, the knowledge of semen quality and its freezability is much imperative. Semen evaluation, a very been of great significance to assess the fertility status of the bull. Conventional parameters used for evaluation of semen have limited application because they only help to assess the structural integrity of the cell (Neild et al., 1999). Season is one of the important factors that influence the semen quality and fertility. Among different seasons hot-dry and hot-humid season is reported to be unfavorable for production as well as reproduction (Bhakat et al., 2011). Season affects the animal directly through macro and micro climatic factors, like temperature, humidity,